Gauging the Influence of New Media on African Narrative Forms and Storytelling: The case of Assase Podcast, Flash Fiction Ghana, and Jalada Africa - Addai-Amoah Kwarteng , Anthony (International Journal of Language and Literary Studies, 2025)
This study examines how African oral narrative forms are being reshaped within digital environments, with a focus on Asase Ba Podcast, Flash Fiction Ghana, and Jalada Africa. Through close reading, content analysis, and contextual interpretation of language, sound, and performance, the study evaluates how these platforms mobilise oral aesthetics in digital formats. Guided by Walter Ong’s Secondary Orality, Performance Theory, and Postcolonial Digital Humanities, the analysis shows that digital media do not merely reproduce traditional oral practices but actively refashion them into hybrid narrative modes. The findings reveal that while digital platforms enhance the reach, dynamism, and participatory potential of oral storytelling, their impact is uneven, shaped by issues of digital access, cultural ownership, and platform politics. Overall, the study argues that African oral traditions are not in decline; rather, they are evolving into innovative, hybridised forms that unsettle rigid distinctions between orality, literacy, and digital culture.